Tracing and Identifying Sources and Types of Pollution in Transitional Arctic Shelf Waters - Lemenkova, Polina (2015)
The papers concerns the advantages of using Quantum GIS for geoinformatics and teaching of mapping and cartographic issues in the classes of geography and Earth sciences. info:eu-repo/semantics/published